Kobiety i sztuka w poezji Wisławy Szymborskiej (uwagi wstępne) = Women and art in Wisława Szymborska`s poetry (initial notes) - Dulko, Katarzyna (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article presents a lexical analysis of Wislawa Szymborska`s works which refer to other texts of culture. The selected texts are examined within the context of the presence of women in art: in painting and literature. Their traditional portrayals are confronted with the image resulting from the poet?s artistic vision, who is trying to break or expand the common thinking of these characters.
Keywords: ekfraza; poezja; kobieta; sztuka; Szymborska, Wisława (1923-2012); ekphrasis; woman; art; poetry